2001
DOI: 10.4049/jimmunol.167.12.6939
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Integrity Between MHC Class II Molecules and Bound Peptide Determines the Intracellular Fate of MHC Class II Molecules

Abstract: MHC class II molecules associate with peptides through pocket interactions and the formation of hydrogen bonds. The current paradigm suggests that the interaction of side chains of the peptide with pockets in the class II molecule is responsible for the formation of stable class II-peptide complexes. However, recent evidence has shown that the formation of hydrogen bonds between genetically conserved residues of the class II molecule and the main chain of the peptide contributes profoundly to peptide stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The authors concluded that the changes to the hydrogen‐bonding network enhanced the transition to the ‘open’ form of the molecule normally catalyzed by DM (110). Sant and colleagues (111) subsequently obtained similar results with I‐A k . Most recently, Stern's group (112) analyzed the ability of DM to catalyze the release of peptides containing mutations that abolished their ability to form hydrogen bonds with the MHC molecule.…”
Section: Unresolved Questionssupporting
confidence: 55%
“…The authors concluded that the changes to the hydrogen‐bonding network enhanced the transition to the ‘open’ form of the molecule normally catalyzed by DM (110). Sant and colleagues (111) subsequently obtained similar results with I‐A k . Most recently, Stern's group (112) analyzed the ability of DM to catalyze the release of peptides containing mutations that abolished their ability to form hydrogen bonds with the MHC molecule.…”
Section: Unresolved Questionssupporting
confidence: 55%
“…It has long been known that peptide ligands extend intracellular class II half-lives (70). Recent evidence suggests that empty or loosely occupied class II is susceptible to proteolytic degradation inside endocytic compartments and at the cell surface (71,72). Allele-and isotype-specific sensitivities to acid-induced denaturation of empty dimers may also selectively influence the elimination of unstable complexes (8,52).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, like class I, the dependence among class II alleles on chaperones is variable, and a naturally occurring mouse MHC class II allele, I‐E k , which has a shallow P1 pocket, was shown to have little dependence upon DM for peptide loading (50). Jensen and colleagues (47) first suggested that DM might act via its ability to accelerate the off‐rate of weak peptides by interrupting the formation of H bonds between key positions in class II and peptide ligand backbone, and this idea has since been strengthened by the observation that I‐A k point mutants, which lack key H‐bond donor side chains (βH81 and βD82), have dissociation rates accelerated by roughly the same degree as wildtype IA k in the presence of DM (51). In addition, Rotzschke and colleagues (52) have demonstrated that small H‐bond donors (such as ethanol) can catalyze ligand exchange on DR in a way that parallels the action of DM (except that it occurs at neutral pH).…”
Section: A Molecular Mechanism For Mhc Class I Complex Optimizationmentioning
confidence: 99%